Analysis of Complete Genomes of Propionibacterium acnes Reveals a Novel Plasmid and Increased Pseudogenes in an Acne Associated Strain. (13th May 2013) - Kasimatis, Gabriela; Fitz-Gibbon, Sorel; Tomida, Shuta; Wong, Marthew; Li, Huiying
Abstract : The human skin harbors a diverse community of bacteria, including the Gram-positive, anaerobic bacterium Propionibacterium acnes . P. acnes has historically been linked to the pathogenesis of acne vulgaris, a common skin disease affecting over 80% of all adolescents in the US. To gain insight into potential P. acnes pathogenic mechanisms, we previously sequenced the complete genome of a P. acnes strain HL096PA1 that is highly associated with acne. In this study, we compared its genome to the first published complete genome KPA171202. HL096PA1 harbors a linear plasmid, pIMPLE-HL096PA1. This is the first described P. acnes plasmid. We also observed a five-fold increase of pseudogenes in HL096PA1, several of which encode proteins in carbohydrate transport and metabolism. In addition, our analysis revealed a few island-like genomic regions that are unique to HL096PA1 and a large genomic inversion spanning the ribosomal operons. Together, these findings offer a basis for understanding P. acnes virulent properties, host adaptation mechanisms, and its potential role in acne pathogenesis at the strain level. Furthermore, the plasmid identified in HL096PA1 may potentially provide a new opportunity for P. acnes genetic manipulation and targeted therapy against specific disease-associated strains.